Land Tenure and the Grassroots’ Concern in Bamako - Lamine Doumbia (Modern Africa, 2018)
The question of the practice of urban land in Bamako is the subject of a crucial (in-)security, which is based both on bureaucratic imbroglio and on an epistemological difference of regularisations of access to the ground through national, regional, municipal institutions and the grassroots. To put an end to the illegal occupation of urban land by the population in need of housing, the state and its representatives have undertaken urban redevelopment measures. Land speculation is taking hold where the State’s intervention capacities do not seem capable to control demographic pressure. Households have been and continue to be evicted by the authorities for projects deemed as “urban redevelopment” or “public utility.” Some citizens have regrouped in Associations that have set themselves the task of combating abuses by the state.